Psychological Well-Being and Life Satisfaction among Rural Island Community in Langkawi, Malaysia - Muhamad Khalil Omar, Norashikin Hussein, Nor Intan Adha Hafit, Nor Azian Abdul Rahman (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Malaysia has demonstrated that the nation is committed to achieving better targets through sustained and systematic efforts for sustainable development goals (SDGs). Targeted at addressing Goal 3 in promoting health and well-being, this study proposed a geopark SDGs study addressing the psychological well-being of the rural community in Tuba Island, Langkawi. The fundamental of psychological well-being is mental health which would reflect the overview of individual health as a whole. Since there is limited evidence on community well-being, thus this study proposed an evaluation platform for community psychological well-being dimensions and how each dimension determines certain job-related outcomes such as job performance and job satisfaction. This study shall employ a quantitative approach through a self-administered survey questionnaire to achieve its objectives. The target respondents are Tuba Island, Langkawi villagers using the purposive sampling method. This study shall be a significant input to policymakers, related ministries and government agencies such as the Ministry of the Rural Development and Langkawi Development Authority (LADA) to increase awareness of psychological well-being among rural communities and formulate and implement development policies for them. This would lead to better community health, enhancing their economic status and well-being as a whole. The most imperative significance of the study is of course to materialize the vision United Nations of world capacity building through various SDGs initiatives.